Striking dynamics and kinetic properties of boxing and MMA gloves (Revista de Artes Marciales Asiáticas, 2014)
With the growing popularity of Mixed Martial Arts (MMA) as a competitive sport, questions regarding the dynamic response and properties of MMA gloves arise. High-energy impacts from punches are very similar to boxing yet MMA competition requires the use of 4 oz fingerless glove, compared to the larger full enclosure boxing glove. This work assessed the kinetic properties and strike dynamics of MMA gloves and compared findings with traditional boxing gloves. Gloves mounted on a molded fist were impacted repetitively on an instrumental anvil designed for impact, over a 5 hour period resulting in 10,000 continuous and consistent strikes. Kinetic data from impacts were sampled at the beginning of the data collection and subsequently every 30 minutes (every 1,000 strikes). MMA gloves produced 4-5 times greater peak force and 5 times faster load rate compared to the boxing glove. However, MMA gloves also showed signs of material fatigue, with peak force increasing by 35% and rate of loading increasing by 60% over the duration of the test. Boxing glove characteristics did deteriorate but to a lesser extent. In summary, the kinetic properties of MMA glove differed substantially from the boxing glove resulting in impacts characterized by higher peak forces and more rapid development of force. Material properties including stiffness and thickness play a role in the kinetic characteristics upon impact, and can be inferred to alter injury mechanisms of blunt force trauma.